2017
DOI: 10.1017/jpa.2017.72
|View full text |Cite
|
Sign up to set email alerts
|

Ichnostratigraphy of the Ediacaran-Cambrian boundary: new insights on lower Cambrian biozonations from the Soltanieh Formation of northern Iran

Abstract: Abstract.-Strata in the Central Alborz Mountains, northern Iran, are interpreted to show continuous sedimentation from Ediacaran through Cambrian times. The Soltanieh Formation consists of five members: Lower Dolomite, Lower Shale, Middle Dolomite, Upper Shale and Upper Dolomite members. The clastic units (Lower and Upper Shale members) represent sedimentation in distal marine settings, ranging from the shelf to offshore, and contain abundant trace fossils of biostratigraphic utility. Four ichnozones have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 118 publications
(240 reference statements)
1
20
0
Order By: Relevance
“…Stöcklin et al, 1964) and occur in the underlying Cíjara Formation. Shahkarami et al (2017) discussed the stratigraphic implications of the Iranian material and comparable material from South China, and concluded that they are not reliable indicators of pre-Cambrian age.…”
Section: Setting Of the Ediacaran-cambrian Boundary Intervalmentioning
confidence: 99%
“…Stöcklin et al, 1964) and occur in the underlying Cíjara Formation. Shahkarami et al (2017) discussed the stratigraphic implications of the Iranian material and comparable material from South China, and concluded that they are not reliable indicators of pre-Cambrian age.…”
Section: Setting Of the Ediacaran-cambrian Boundary Intervalmentioning
confidence: 99%
“…Moreover, a remarkable negative δ 13 C excursion (-7 to -9 ‰) has been identified at the middle of the LSM, and was globally linked to an isotopic anomaly due to oceanic environmental change just before the PC-C boundary (Kimura et al 1997). Shahkarami, Mángano & Buatois (2017) proposed the new position for the PC-C boundary based on the report of Hyolithellus sp. from the LDM in the Vali-Abad section by Hamdi, Brasier & Zhiwen (1989), and new sedimentological data from the Garmab and the Type section in Zanjan (Fig.…”
Section: Geological Setting and Stratigraphy Of The Soltanieh Formationmentioning
confidence: 99%
“…The PC-C boundary is located almost at the top of the Lower Shale Member of the Soltanieh Formation, 200-300 m above its basal contact with the Kahar Formation as documented by biostratigraphic data (Hamdi, Brasier & Zhiwen, 1989;Ciabeghodsi et al 2005Ciabeghodsi et al , 2006Ciabeghodsi, 2007;Jafari, Shemirani & Hamdi, 2007;Ghorbani, 2013). However, Shahkarami, Mángano & Buatois (2017) have recently suggested that the Ediacaran-Cambrian boundary is located at the base of the Soltanieh Formation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Kushk Series is extensive and well exposed in the region, with a measured thickness of more than 500 m in some areas, and is known for its black shales that host economically viable lead-zinc deposits (Yaghubpur and Mehrabi 1997;Rajabi et al 2014;Rajabi et al 2012a). The Kushk Series represents a relatively deep-water paleo-environment when compared to the northern fossiliferous Soltanieh Formation (Stöcklin et al 1964;Shahkarami et al 2017a;Shahkarami et al 2017b), allowing for comparisons of fossil diversity and community ecology across a major bathymetric divide across the Ediacaran-Cambrian boundary.…”
Section: Introductionmentioning
confidence: 99%